Novel perylene liquid crystals: Investigation of the influence of bay-substituents on mesomorphism and photophysical property. (October 2016) - Zhu, Mingguang; Guo, Hongyu; Yang, Fafu; Wang, Zusheng
Abstract: A series of perylene liquid crystals with H, Br, phenyl and tert -butylphenyl on bay-positions were synthesized in yields of 50–70%. Their mesomorphic properties and photophysical properties were investigated. The perylene derivatives 6, 7 and 8 with Br, phenyl and tert -butylphenyl at bay-positions have the hexagonal columnar liquid crystalline phase and wider scopes of phase transfer temperatures in comparison with similar perylene liquid crystal 5 with no substituent on bay-position. Compounds 6, 7 and 8 showed stronger fluorescence intensities, larger Stokes shifts and higher quantum yields than that of compound 5. These results indicated that the suitable substituents on bay-positions of perylene liquid crystals were favorable for producing excellent mesomorphic properties and good fluorescence properties. Graphical abstract: Highlights: Novel perylene liquid crystals with different bay-substituents were prepared. They have good Colh mesophase and fluorescence properties. They possess wide scopes of mesophase transfer temperatures. The suitable bay-substituents were favorable for mesophase and fluorescence.